Giant orbital cavernous hemangioma: A case report - (:unkn) unknown (MOSBY, INC, 2005)
Cavernous hemangiomas are one of the most common benign primary orbital vascular tumors that almost always occur unilaterally.(1,2) These vascular lesions are slowly growing, relatively painless tumors occurring in middle-aged adults with a female preponderance.(1,3,4) Clinical manifestations of the orbital cavernous hemangiomas depend on the mass effect with ocular problems and facial deformity. A conspicuous feature of these tumors is the preservation of normal visual function and ocular mobility in the presence of progressive proptosis from tumor growth.(1) Although small and asymptomatic lesions usually require periodic observation, most authors recommend en bloc excision as soon as the diagnosis is established.(3) In the present article, we report the diagnosis and treatment of a case of a giant cavernous hemangioma of the orbit causing complete visual loss in a male patient.
Keywords: REMOVAL